FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELENGKAPAN DOKUMEN REKAM MEDIS RAWAT INAP DI RUMAH SAKIT TAHUN 2018 - Anna Anita Paulus; Yudhy Dharmawan; Farid Agushybana (Jurnal Kesehatan Masyarakat, 2019)
Factors Are Related To Complete Of Medical Record Documents In Hospital In 2018The completeness of medical record document is one of the factors in assessing the quality of data in health information system. At Pertamina Cirebon Hospital, there are still incomplete filling of medical record documents. The purpose of the study was to analyze the some factors related to the completeness of medical record documents. The method used explanatory research with cross sectional study approach. The research sample was 90 medical record documents. Data analysis consisted of univariate and bivariate. Univariat analysis showed average completeness medical records by doctors is 88%, and the average completeness medical records by nurses is 89%. The perfomance index of the doctor's knowledge variable was 75,45 and the nurse was 85,82. The perfomance index of the doctor's motivation variable was 83,8 and the nurse was 78,47. The perfomance index of the doctor's communication variable was 83,1 and the nurse was 84,1. The perfomance index of doctor reward variable is 68,16 and nurse is 73,15. The perfomance index of the variable in the complexity of the doctor's form was 79,05 and the nurse was 80,87. The perfomance index of the doctor's leadership variable was 80,81 and the nurse was 79,3. The perfomance index of the doctor's supervision variable was 76,25 and nurses was 78,67. Bivariate analysis shows that there is a relationship between doctor's communication (p = 0,012), complexity of the doctor (p = 0,006), doctor's leadership (p = 0,015), nurse's leadership (p = 0,026), nurse supervision (p = 0,02) with completeness of medical record. Recommendations to Pertamina Hospital that supervision is carried out routinely and programmed and can increase the motivation of doctors and nurses in filling medical record documents.Keywords: completeness, medical record, determinant factors.